AB0874 Assessment of spinal mobility improvement in an education and home excercise program for ankylosing spondylitis patients using a motion capture system. (23rd January 2014) - Collantes, E.; Garrido-Castro, J.L.; Medina, R.; Galisteo, A.M.; Gonzalez, C.; Ruiz, D.; Font, P.; Gomariz, E.M.
Abstract : Background: A study on 622 patients diagnosed with ankylosing spondylitis were realized by researchers of GRESSER Group [1]. They were randomized to an education intervention or standard care. The intervention included an informative session and a physical activity program at home. Education group diminished activity of the disease with significant reductions in VAS, BASDAI, BASFI and ASQoL. 30 participated at the Reina Sofia University Hospital where more exhaustive metrology were applied using a motion capture system. Objectives: To assess spinal mobility improvements on patients included in an education program using a motion capture system. Methods: On 30 patients with AS, we used a motion capture system (UCOTrack) to assess spinal mobility. 15 were included in the education group and 15 in control group. Two measurements were made at the beginning and at the end of the activity (6 months) in both groups. Some 3D new measures were defined, including UCOASMI (an index based on 5 measurements), although conventional measurements were obtained using the system. VAS, BASDAI, BASFI, ASQoL and BASMI were also evaluated. Results: Mean values and standard deviations of different parameters are shown in table.To analyze response, mean difference and coefficient of variation of both groups are shown with statistically significant differences (*P<0.05). Conclusions: Our results confirm a significant decrease in activity indicators of education group, like previous mentioned studies. But there isn't significant improvement in mobility, in contrast to other more active interventions as physiotherapy, hydrotherapy, biological therapies, etc. However, in some measurements, there have been significant differences, specially in UCOASMI. Motion capture has proven to be more sensitive in assessing mobility and can be a useful tool to analyze change in patient's physical condition. References: Rodriguez-Lozano et al. Outcome of an Education and Home Exercise Program for Ankylosing Spondylitis Patients: A Nationwide Randomized Study. Arthritis Rheum 2010, 62 Suppl 10, 2268. Disclosure of Interest: None Declared